Proposal to implement the Balanced Scorecard in a nonprofit organization - Quesado, Patricia (2017)
In this paper we aim to develop a Balanced Scorecard (BSC) model for a nonprofit organization whose activity focuses on the teaching of chess. In order to answer the research question, we have carried out a qualitative research based on the case study. Our study is characterized by a descriptive analysis. The results allow us to conclude that the BSC is a tool that will allow to define the strategy in a clearer and objective way, allowing a greater awareness of the importance of an internal organization that allows to reach the defined objectives through a set of initiatives. The study presents a contribution to the current state of knowledge, since we seek to provide the organization with a management tool that allows to measure its performance and the value it adds to society and to outline a consistent and sustainable long-term strategy. In addition, a theoretical basis is provided for subsequent research, evidencing the breadth of research on the topic studied.